2021
DOI: 10.1097/yct.0000000000000782
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Change in Depressive Symptoms and Inflammatory Markers After Electroconvulsive Therapy

Abstract: Depression is a major mental health disorder, and its pathophysiology is still largely unknown, as is the action mechanism of electroconvulsive therapy (ECT). Some evidence suggests that inflammation might play a role in depression, and several studies have attempted to demonstrate a link between ECT and cytokines. This systematic review used a qualitative analysis to assess the effect of ECT on inflammatory markers as it relates to the clinical response of depressive symptoms in major depressive disorders. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…One possibility is that ECT’s robust neuroplastic effects within the temporal lobe are related to the modulation of the LDAEP. Moreover, systematic reviews found that ECT has consistently been reported to decrease levels of inflammatory biomarkers, tumor necrosis factor alpha (TNF- α ) and interleukin-6 (IL-6) (83, 84). Notably, one study demonstrated that the LDAEP was negatively correlated with TNF- α (85).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that ECT’s robust neuroplastic effects within the temporal lobe are related to the modulation of the LDAEP. Moreover, systematic reviews found that ECT has consistently been reported to decrease levels of inflammatory biomarkers, tumor necrosis factor alpha (TNF- α ) and interleukin-6 (IL-6) (83, 84). Notably, one study demonstrated that the LDAEP was negatively correlated with TNF- α (85).…”
Section: Discussionmentioning
confidence: 99%
“…Various biological treatment regimes, including pharmacotherapy and noninvasive brain stimulation with electroconvulsive therapy, indeed led to a reduction of pro-inflammatory markers, highlighting the role of inflammation in psychiatric vulnerability. 39 , 40 Next to inflammatory pathways leading to both autoimmune hypothyroidism and increased psychiatric vulnerability, coinciding autoimmune disorders might also for other reasons than shared inflammatory pathways be responsible for the observed relationships between thyroid and psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, studies on inflammatory biomarkers have been unable to detect markers that are specific for any particular psychiatric disorder, thereby suggesting genetic variation in autoimmunity to be a more general underlying phenomenon. Various biological treatment regimes, including pharmacotherapy and non-invasive brain stimulation with electroconvulsive therapy (ECT) indeed lead to a reduction of pro-inflammatory markers, highlighting the role of inflammation in psychiatric vulnerability [36, 37]. Next to inflammatory pathways leading to both autoimmune hypothyroidism and increased psychiatric vulnerability, coinciding autoimmune disorders might also for other reasons than shared inflammatory pathways be responsible for the observed relations between thyroid and psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%